(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2020)
The Philippines nowadays has become more vulnerable to the risk of an earthquake, which can result in infrastructure collision that can lead to severe physical and emotional injuries or even death. An earthquake-resistant house model has been developed as a solution to the aforementioned problem. Earthquake-resistant houses are structures that can withstand the sudden movement of the ground produced by an earthquake. The purpose of the study was to minimize the casualties and damages caused by an earthquake. This study utilized a quantitative experimental research design and used purposive sampling to select five civil engineers, give mechanical engineers, and five architects as respondents to assess the level of acceptability of the proposed Philippine modern houses that are resilient from earthquake damages. Materials used, the template of the floor plan, and the initiation of the process was performed to construct the earthquake-resistant house model. Using a questionnaire, the researchers conducted a survey to determine whether the project is acceptable. The result of the study in terms of construction materials, procedural methodology, mechanism, stability/durability, and presentation was moderately acceptable. The degree of freedom between groups was 2, while that within groups was 12, with the total of 14. The sum of squares between groups obtained 111.24, while that within groups obtained 111.13, with a total sum of squares of 222.37. The F-variance ∝=0.01 of between groups and within groups obtained 6.93. The f-computed value of the between groups and within groups was 6.01. The F-variance value was greater than the F-computed one. Therefore, the remarks of the between groups and within groups are to accept Ho. This result indicated that the difference between and among the assessment of the three groups of respondents in the level of acceptability of the earthquake-resistant house model in terms of construction of materials, procedural methodology, mechanism, stability/durability, and the presentation was not significant. The recommendations of the three groups of respondents are as follows: use cement for the house instead of cardboard, present structural design for the basis of evaluation, the base isolation system should have some reported stiffness in terms of force over length, scale model should be the proper replica of the actual model, and each part should be affixed properly.